Psychological benefits of a biodiversity-focussed outdoor learning program for primary school children - Harvey, Deborah J.; Montgomery, Louise N.; Harvey, Hannah; Hall, Felix; Gange, Alan C.; Watling, Dawn (Journal of Environmental Psychology, 2020)
This investigation sought to discover whether engaging school children (aged 8–11) with nature could produce sustained improvements in mood and wellbeing in the long-term. We designed a program of biodiversity-focused activities carried out over one academic year in the school grounds. Participation in this program produced significant improvements in children's mood and wellbeing, which were sustained across the academic year. Improvements in wellbeing were not found in a control sample of children who did not take part in the activities. Children with initially lower feelings of connection to nature became more connected over the course of their participation. Building engagement with nature into school curricula could therefore be a low-cost way to improve children's psychological wellbeing.
Keywords: Biodiversity; Biophilia; Mood; Outdoor education; Primary education; Wellbeing